EFhd2 co-aggregates with monomeric and filamentous tau in vitro - Soliman, Ahlam S.; Umstead, Andrew; Lamp, Jared; Vega, Irving E. (Frontiers in Neuroscience, 2024)
Tauopathies are characterized by the abnormal buildup of tau protein, with early oligomeric forms associated with neurodegeneration and the later neurofibrillary tangles possibly conferring neuroprotection. The molecular mechanisms governing the formation of these tau species are unclear. Lately, there has been an increased focus on examining the interactions between tau and other proteins, along with their influence on the aggregation of tau. Our previous work revealed EFhd2’s association with pathological tau in animal models and tauopathy brains. Herein, we examined the impact of EFhd2 on monomeric and filamentous tau in vitro. The results demonstrated that EFhd2 incubation with monomeric full length human tau (hTau40) formed amorphous aggregates, where both EFhd2 and hTau40 colocalized. Moreover, EFhd2 is entangled with arachidonic acid (ARA)-induced filamentous hTau40. Furthermore, EFhd2-induced aggregation with monomeric and filamentous hTau40 is EFhd2 concentration dependent. Using sandwich ELISA assays, we assessed the reactivity of TOC1 and Alz50—two conformation-specific tau antibodies—to EFhd2-hTau40 aggregates (in absence and presence of ARA). No TOC1 signal was detected in EFhd2 aggregates with monomeric hTau40 whereas EFhd2 aggregates with hTau in the presence of ARA showed a higher signal compared to hTau40 filaments. In contrast, EFhd2 aggregates with both monomeric and filamentous hTau40 reduced Alz50 reactivity. Taken together, our results illustrate for the first time that EFhd2, a tau-associated protein, interacts with monomeric and filamentous hTau40 to form large aggregates that are starkly different from tau oligomers and filaments. Given these findings and previous research, we hypothesize that EFhd2 may play a role in the formation of tau aggregates. Nevertheless, further in vivo studies are imperative to test this hypothesis.